2020
DOI: 10.1088/1757-899x/805/1/012041
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, bioactivities and cytogenotoxicity of animal fur-mediated silver nanoparticles

Abstract: Animal waste materials are rarely used in the synthesis of nanoparticles compared to microorganisms and plant materials. The use of animal fur (goat) in synthesis could assist in turning waste to wealth. Thus, potentials of animal fur in the synthesis of silver nanoparticles (AF-AgNPs), its biological activities and safety through cytogenotoxicity were investigated. Animal fur (1 g) was hydrolyzed with 100 ml of 0.1 M NaOH at 90 °C for 1 h, cooled and centrifuged at 4000 rpm for 30 min. The extract (1 ml) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(34 citation statements)
references
References 49 publications
2
32
0
Order By: Relevance
“…Different AgNPs formulations are available in the market differing in shape, size distribution, the content of metallic silver, synthesis procedure, surface functionalization, and coating agent of the nanoparticles [16][17][18]. All these features help nanoparticles to reach and interact with a wide range of biological targets, playing a significant role in the cytotoxic effects exerted [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Different AgNPs formulations are available in the market differing in shape, size distribution, the content of metallic silver, synthesis procedure, surface functionalization, and coating agent of the nanoparticles [16][17][18]. All these features help nanoparticles to reach and interact with a wide range of biological targets, playing a significant role in the cytotoxic effects exerted [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is necessary to develop an environment friendly method to synthesize AgNPs using gentle techniques and nontoxic chemicals during the synthesis process 12,13 . Recently, application of biomaterials for AgNPs synthesis have attracted the attention of investigators, the biomaterials include plant, fungi, bacteria and algae, metabolites of arthropods, enzymes animal and agricultural wastes materials et al [14][15][16][17][18][19][20][21][22][23] .Fungi can produce large amount of metabolites compared to other microorganisms, making it more suitable for nanoparticles production 24,25 . Many articles have reported that fungi have the ability to synthesize nanoparticles 26,27 .…”
mentioning
confidence: 99%
“…7 These have been used to improve various approaches by mimicking the nucleation abilities found in redox biomolecules from living organisms for nanoparticle synthesis. 8 However, not only have microorganisms and plants and their metabolites or associated enzymes been used for the synthesis of AgNPs, but also insect and animal derivatives, such as honey 9 and fur, 10 which are considered reliable candidates because of their intrinsic properties such as the presence of enzymes and polyphenols. [11][12][13] Fungi can produce oxide-reductive extracellular metabolites that play a key role in the biosynthesis of AgNPs, 14 such as laccase and xylene, 15 although the use of fungal cell cultures has some drawbacks, mainly related to the large amounts of enzymes or metabolites in adequate concentrations for the synthesis process.…”
Section: Introductionmentioning
confidence: 99%